(3GOGQI GddhLjSJjGJ (B:s (3GdTQGA(B-(3GdJNRjf(B-(3GdJhRjY (B/s - (3UGHQ, eMeO YHO GdYdjes ((3GdGScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2008)
(3jYGdL gPG GdcJGH(B:(3eaGgje aj EOGQI GddhLSJjGJ,YedjGJ GddhLSJjjGJ,CfTWI GdJfSjb Hjf YedjGJ GddhLjSJjGJ,EOGQI SdGSd GdJhQjO,hXjaI GdTQGA Gdfbd hGdJhRjY,EOGQI GdeNRhf,GdQbGHI Ydi GdeNRhf,EOGQI GdeNGRf hefGhdI GdehGO hGdJZdja,JfXje EOGQI GddhLSJjjGJ(B. s
Keywords: (3GOGQIs; (3GdJNRjfs; (3GddhLjSJjGJs; (3JhRjYs; (3TQGAs